APOBEC3B reporter myeloma cell lines identify DNA damage response pathways leading to APOBEC3B expression. - Hiroyuki Yamazaki; Kotaro Shirakawa; Tadahiko Matsumoto; Yasuhiro Kazuma; Hiroyuki Matsui; Yoshihito Horisawa; Emani Stanford; Anamaria Daniela Sarca; Ryutaro Shirakawa; Keisuke Shindo; Akifumi Takaori-Kondo (PLoS ONE)
Apolipoprotein B mRNA-editing enzyme catalytic polypeptide-like (APOBEC) DNA cytosine deaminase 3B (A3B) is a DNA editing enzyme which induces genomic DNA mutations in multiple myeloma and in various other cancers. APOBEC family proteins are highly homologous so it is especially difficult to investigate the biology of specifically A3B in cancer cells. To easily and comprehensively investigate A3B function in myeloma cells, we used CRISPR/Cas9 to generate A3B reporter cells that contain 3×FLAG tag and IRES-EGFP sequences integrated at the end of the A3B gene. These reporter cells stably express 3xFLAG tagged A3B and the reporter EGFP and this expression is enhanced by known stimuli, such as PMA. Conversely, shRNA knockdown of A3B decreased EGFP fluorescence and 3xFLAG tagged A3B protein levels. We screened a series of anticancer treatments using these cell lines and identified that most conventional therapies, such as antimetabolites or radiation, exacerbated endogenous A3B expression, but recent molecular targeted therapeutics, including bortezomib, lenalidomide and elotuzumab, did not. Furthermore, chemical inhibition of ATM, ATR and DNA-PK suppressed EGFP expression upon treatment with antimetabolites. These results suggest that DNA damage triggers A3B expression through ATM, ATR and DNA-PK signaling.